PENGARUH PEMBERIAN VARIAN HERBAL JAHE (Zingiber officinale) DENGAN AUTOMATIC FEEDER TERHADAP PANJANG TUNGKAI (FEMUR, TIBIA, METATARSO) PADA ITIK (Anas javanicus) - Reni Rakhmawati; Mei Sulistyoningsih (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
This study aims to determine the effect of giving ginger elephant and ginger empiric herbs by using automatic feeder or manual feed tool to the length of the leg bones (femur, tibia, metatarso) in ducks. This study used randomized randomized controlled trials with four treatments and three repetitions. GP1 (Feed + Automatic Feeder + Elephant Ginger 2%), GP2 (Feed + Manual + Elephant Ginger 2%), EP1 (Feed + Automatic Feeder + Emprit Ginger 2%), EP 2 (Feed + Manual + Empritic Ginger 2%). The parameters measured were the length of the leg bones (femur, tibia, metatarso) of ducks. The results of the analysis showed that the total bone length of the femur was 6.51 cm with Fcount (0.038) <Ftable (5.32), the total length of the total tibia bone was 11.9 cm with Fcount (1,313) <Ftable (5, 32), and the results of the total length of the metatarso bone are 6.67 cm with Fcount (0.668)> Ftable (5.32). These results indicate that the effect of giving ginger elephant and empirical ginger using a feed device Automatic feeder or manually has no significant effect (P> 0.05) on the length of the leg bones (femur, tibia, metatarso) of ducks. The results are not significantly different which causes the Automatic feeder tool to be a new breakthrough for replacing the manual feed tool for feeding ducks